2019
DOI: 10.3390/mi10060370
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Micromachine Using Nickel Nanoparticles for Propelling and Releasing in Indirect Assembly of Cell-Laden Micromodules

Abstract: Magnetic micromachines as wireless end-effectors have been widely applied for drug discovery and regenerative medicine. Yet, the magnetic assembly of arbitrarily shaped cellular microstructures with high efficiency and flexibility still remains a big challenge. Here, a novel clamp-shape micromachine using magnetic nanoparticles was developed for the indirect untethered bioassembly. With a multi-layer template, the nickel nanoparticles were mixed with polydimethylsiloxane (PDMS) for mold replication of the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In this sense, ferromagnetic liquids open up an entirely new world of magnetic materials benefiting from mechanical and magnetic reconfigurability; for instance, 3D printed water-in-oil magnetic liquid tubules offer arbitrary shape (fluidity) and self-adaptive permanent magnetization (solidity), which benefit magnetic liquid actuators, non-contact liquid capsule delivery and other magnetically controlled devices in all-liquid environment. Magnetically driven autonomous technology often relates to the parallelized and sequential operations with respect to actuators in medical diagnostics, non-contact delivery and chemicals synthesis [56][57][58][59][60][61][62][63]. Reconfigurable ferromagnetic liquids representing magnetic liquid actuators and sensors, interact with the external magnetic field to exert translation and precession movement that can be facilitated in analogy to solid-state magnets.…”
Section: Technological Perspectivementioning
confidence: 99%
“…In this sense, ferromagnetic liquids open up an entirely new world of magnetic materials benefiting from mechanical and magnetic reconfigurability; for instance, 3D printed water-in-oil magnetic liquid tubules offer arbitrary shape (fluidity) and self-adaptive permanent magnetization (solidity), which benefit magnetic liquid actuators, non-contact liquid capsule delivery and other magnetically controlled devices in all-liquid environment. Magnetically driven autonomous technology often relates to the parallelized and sequential operations with respect to actuators in medical diagnostics, non-contact delivery and chemicals synthesis [56][57][58][59][60][61][62][63]. Reconfigurable ferromagnetic liquids representing magnetic liquid actuators and sensors, interact with the external magnetic field to exert translation and precession movement that can be facilitated in analogy to solid-state magnets.…”
Section: Technological Perspectivementioning
confidence: 99%
“…Copyright 2016, Wiley. Panel (h): Reproduced under the terms of the CC BY 4.0 license . Copyright 2019, The Authors, published by MDPI.…”
Section: Magnetic Actuation Systemsmentioning
confidence: 99%
“…Le et al designed a system with eight electromagnets placed in three dimensions at 90° with respect to one another, as shown in Figure g . The eight electromagnets of the system in Figure h are arranged at each vertex of a cube and with each pointing to the center …”
Section: Magnetic Actuation Systemsmentioning
confidence: 99%
“…These constructs were modified to mimic blood vessels, by making a hole in the center of the micromodule. 106 Results showed that indirect magnetic manipulation is an efficient and versatile bioassembly method for cellular micromodules, and the high level of cell viability makes these structures of potential interest for drug screening.…”
Section: Bioassembled In Vitro Tissue Modelsmentioning
confidence: 99%